Dacomitinib for the treatment of advanced or metastatic non-small-cell lung cancer. (April 2014) - Mok, Tony; Lee, Kirsty; Tang, Michael; Leung, Linda
ABSTRACT: : Dacomitinib (PF-00299804) is a second-generation irreversible HER tyrosine kinase inhibitor (TKI). In preclinical studies, dacomitinib has demonstrated anti-tumor activity in lung cancer cell lines with sensitive and resistant EGFR mutations (including the T790 mutation). Safety and well tolerability of dacomitinib were demonstrated in Phase I studies with stomatitis, diarrhea and skin toxicities being the dose-limiting toxicities. The maximum tolerated dose was established to be 45 mg/day. In Phase II and III studies, dacomitinib has shown clinical activity in both HER tyrosine kinase-naive and HER tyrosine kinase failure settings. Further clinical trials are underway to evaluate the efficacy of dacomitinib in non-small-cell lung cancer.